O coral vozes da infância: um olhar sobre as concepções em torno das práticas músico-educativas - Lima, Christiane Alves de (2018)
Children's choral singing comprises a learning environment of great relevance not only for the musical characteristics but also for the process of recognition of its members as individuals and as part of a whole. Through choral singing, as in other musico-educational practices, children and adolescents have the opportunity to broaden their cultural universes and deal with difference, enabling the development of new ways of thinking and acting in their daily lives. Therefore, this study has as its theme the musical education processes developed in the context of the Voices of Childhood Choir of the Municipal School of Art - Casa das Artes (EMA-CA) in the city of João Pessoa-PB. The Choir consists of children and adolescents between the ages of 10 and 15, involving students from the fifth to the ninth grade of municipal schools in João Pessoa and the community in general. Thus, this work has as general objective to identify and to understand the main conceptions around the musico-educative practices of the Choir Voices of Childhood. The specific objectives are to identify and understand: the main characteristics of the musician-formative practices of the Choir; the conceptions of choristers, teachers, directors and family members responsible for choristers; and the main relations between the musician-educational practices and the conceptions of the investigated subjects. The work is mainly based in the field of music education and related areas, such as education and sociology. The methodology was developed from a qualitative approach, outlined as a case study and based on bibliographical research, participant observation and interviews with choristers, relatives responsible for choristers, directors of the basic school in which students are part, music team and coordinator of EMA-CA. The procedures of organization and analysis of the data were conducted from the theoretical framework; description and analysis of coral activities; transcription and interview analysis; triangulation of information; and qualitative interpretative analysis. The results point to a collective construction based on the social interaction between choristers, allowing personal and group growth leading to the expansion of the world and to human formation. Thus, the work developed points to: 1) the perception of a diversified research panorama on musician-educational processes in choral singing, indicating the main contexts and epistemological dimensions that have built the main currents on the subject; 2) some interpretive possibilities of the reality of study from the theoretical perspectives on musical education as a human formation, based on ethics and cultural diversity, passing through aspects such as collective, individual and collective identity, as well as the production of meanings around from music; and 3) the perception of a formation structure in the Choral Voices of Childhood based on technical aspects about choral singing but permeated by social situations and possibly articulating interpersonal relationships and human formation. 4) the results point to the understanding of the main conceptions around the musician-educational practices based on the theoretical reference and the process of triangulation of the data involving the empirical knowledge, interviews dialoguing with the theoretical reference. We identified in the interviews conceptions that the choristers themselves formed around the choir like, the idea of belonging and the "we". In analyzing the speeches of the legal heads of the choristers I identified that the work developed in the choir and the changes in the behavior of the members were reflected in their homes. We noticed that there were positive changes in the behavior of its members, making it possible to broaden the world view through the mechanisms of social interaction developed in the choral environment, contributing to the process of human formation.